Versatile, scalable, and accurate simulation of distributed applications and platforms - Casanova, Henri; Giersch, Arnaud; Legrand, Arnaud; Quinson, Martin; Suter, Frédéric (Journal of parallel and distributed computing, 2014)
The study of parallel and distributed applications and platforms, whether in the cluster, grid, peer-to-peer, volunteer, or cloud computing domain, often mandates empirical evaluation of proposed algorithmic and system solutions via simulation. Unlike direct experimentation via an application deployment on a real-world testbed, simulation enables fully repeatable and configurable experiments for arbitrary hypothetical scenarios. Two key concerns are accuracy (so that simulation results are scientifically sound) and scalability (so that simulation experiments can be fast and memory-efficient). While the scalability of a simulator is easily measured, the accuracy of many state-of-the-art simulators is largely unknown because they have not been sufficiently validated. In this work we describe recent accuracy and scalability advances made in the context of the SimGrid simulation framework. A design goal of SimGrid is that it should be versatile, i.e., applicable across all aforementioned domains. We present quantitative results that show that SimGrid compares favorably with state-of-the-art domain-specific simulators in terms of scalability, accuracy, or the trade-off between the two. An important implication is that, contrary to popular wisdom, striving for versatility in a simulator is not an impediment but instead is conducive to improving both accuracy and scalability. •We provide a presentation of the improvements done in SimGrid in the last 10 years.•We rebut popular wisdom that specialization allows for “better” simulation.•We claim that versatility leads to better accuracy and better scalability.•We back up this claim with multiple use cases and (in)validation studies.